Testing The Construct Validity Of A Proposed Measurement Model Of Mobile Applications In The Learning Process Using Confirmatory Factor Analysis - Altaher Alssaid M Alssaid; Noorhayati Binti Hashim; Noor Azizi Ismail (International Journal of Science and Research (IJSR), 2024)
The present study to test the validity of a proposed research model to measuring mobile phone applications in the learning process at the faculties physical education-Libya through several dimensions characteristics, possibilities, importance and readiness. In order to achieve this, the researchers used a Confirmatory Factor Analysis (CFA) through the Amos program. The results of the analysis showed that the proposed research model was valid, and it can be relied upon to be used for measuring mobile phone applications in the learning process.